13 hours [videorecording (DVD)] : the secret soldiers of Benghazi - Krasinski, John, 1979-; Dale, James Badge, 1978-; Schreiber, Pablo; Zuckoff, Mitchell (Paramount, 2016)
A gripping true story of six elite ex-military operators assigned to protect the CIA who fought back against overwhelming odds when terrorists attacked in the U.S. diplomatic compound on September 11, 2012. When everything went wrong, six men had the courage to do what was right.